Entrepreneurship and regional economic development : a spatial perspective - Groot, Henri L. F. de; Nijkamp, Peter; Stough, Roger (Cheltenham, U.K. ; Northhampton, Mass. : Edward Elgar, 2004)
This book provides a theoretical and empirical analysis of entrepreneurial behaviour in a spatial context, and links it to important new fields in economics such as endogenous growth theory, the new economic geography and evolutionary theory. Examines the spatial variation in entrepreneurial activity and the implications of this for regional policy.
Includes bibliographical references and index.
oif 12/02/15
Loan
Keywords: Entrepreneurship; Regional planning